Radio-television-cable management - Brown, James A. (James Anthony), 1932-; Quaal, Ward L. (Boston : McGraw-Hill, 1998)
Managing electronic mass media systems. Theories of managing. Principles of managing and the manager's role. Profiles of middle managers. Managing media personnel. Managers and media Audiences. Managing local programming. Managers and national programming...
Keywords: Radio broadcasting; Television broadcasting; Radio broadcasting -- United States -- Management; Television broadcasting -- United States -- Management